Bayesian and Multivariate Analyses of combined molecular and morphological data in Linum austriacum (Linaceae) populations: Evidence for infraspecific taxonomic groups (Biodiversitas Journal of Biological Diversity, 2015)
Afshar F, Sheidai M, Talebi SM, Keshavarzi M. 2015. Bayesian and Multivariate Analyses of combined molecular andmorphological data in Linum austriacum (Linaceae) populations: Evidence for infraspecific taxonomic groups. Biodiversitas 16: 179-187. Plant specimens of Linum austriacum (Linaceae) were collected from 16 geographical populations of nine provinces in Iran andused for morphological and molecular (ISSR) analyses. Different multivariate and Bayesian methods were used to studyinterpopulations differences. Analysis of variance test and Principal coordinate analysis plots indicated morphological difference of thepopulations. Mantel test revealed positive significant correlation between morphological and geographical distance of these populations.Pearson, coefficient of correlation showed significant correlations between basal leaf length, width and length/width ratio with latitudeand altitude of the studied populations. Bayesian analysis of combined molecular and morphological features revealed divergence of thestudied populations and consensus tree showed separation of 6 populations in different clusters. Canonical Variate Analysis plot of thesepopulations showed that Sang Sefid and Salmas populations differed greatly from the other populations. New ecotypes are suggested forthese populations.
Keywords: Infraspecific variation, morphology, Iran, ISSR, population.